Strategi Media Relations Pt. Angkasa Pura Ii Di Bandar Udara Fatmawati Soekarno Bengkulu - Beny Fernando; Anis Endang; Sri Narti (Universitas Dehasen Bengkulu, 2024)
The aim of the research is to determine the media relations strategy carried out by PT Angkasa Pura II at Fatmawati Bengkulu Airport in fostering good relations with the media. This research uses the Four-step Public Relations Process theory by taking the six media PR strategies proposed by Frank Jefkins. This type of research uses a qualitative approach with data collection techniques through observation, in-depth interviews and documentation. The results of this research can be concluded that PT. Angkasa Pura II at Fatmawati Bengkulu Airport in building good relations with the media, namely carrying out various activities such as invitations for coverage at the airport terminal, media visits and providing a wifi network for the media. Apart from that, there are obstacles, namely the large number of media who find it difficult to attend the activities being held.